2008
DOI: 10.1111/j.1365-2044.2008.05674.x
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐operative use of paracetamol

Abstract: SummaryThis article is a review of the peri-operative use of paracetamol. It reviews the pharmacology of paracetamol, highlighting new information about the mechanism of action, and examines its therapeutic use in the peri-operative period, focusing on efficacy, route of administration, and the use of a loading dose to improve early postoperative analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 76 publications
0
74
0
14
Order By: Relevance
“…It is absorbed rapidly and well from the small intestine after oral administration with a bioavailability of between 63% and 89% (Oscier & Milner, 2009). It can also be given rectally and intravenously (see below and Section 6).…”
Section: Paracetamolmentioning
confidence: 99%
See 1 more Smart Citation
“…It is absorbed rapidly and well from the small intestine after oral administration with a bioavailability of between 63% and 89% (Oscier & Milner, 2009). It can also be given rectally and intravenously (see below and Section 6).…”
Section: Paracetamolmentioning
confidence: 99%
“…The effects of the analgesics may vary with different pain models (Gray et al, 2005 Level I; Oscier & Milner, 2009 …”
Section: Chaptermentioning
confidence: 99%
“…The lack of a significant anti-inflammatory activity of paracetamol implies a mode of action which is distinct from that of the non-steroidal antiinflammatory drugs. Yet, the Cochrane Systematic Review, 2004 concluded that paracetamol was effective against the postoperative pain in adults [23].…”
Section: Clinical Trials On Analgesicsmentioning
confidence: 99%
“…Acetaminophen was selected due to its widespread use as an analgesic and because it has been thoroughly studied by many researchers. In comparison to other drugs, its systemic mechanism of action is satisfactory, although large-scale use has been shown to cause serious liver damage [14,15]. However, this side effect is not as relevant for the field of dentistry, as drugs for this use are generally administered for only a short period.…”
Section: Doi: 107243/2053-5775-1-4mentioning
confidence: 99%